Survey in Western Iran, 1961 - Young, Jr., T. Cuyler
Geography – Pottery Found and its Distribution: 1. Early, straw-tempered wares; 2. Third and second millennium wares; 3. Late second millennium to Islamic wares – Chronology and Conclusions – Site List: Khakriz; Bozan; Jannatabad; Phil; Ahmadabad; Bad Khoreh; Musiabad; Shanazar; Guch; Mendarabad; Godin; Kar Khaneh; Sarab; Sahneh; Fazabad; Gurgavan; Malamiri Sofla; Faraghan; Pa-i-Qal‛eh; Firuzabad; Shurcheh; Khamisabad; Barafraq; Giyan; Baba Qassem, Asad Khani; Rahimabad, Bozaznah; Gachineh; Qal‛ah-i-No; Pishkildun; Qoroq; Qa‛lehabadi; Belah; Zague; Bog-i-No; Zahed; Malikabad; Taqiabad; Kiakulah; Sonbedan; Gavkoshah; Darband; Qal‛eh Kharab; Chagah Guni; Ali-Gudarz; Jangah.